2013
DOI: 10.1021/jf304150b
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Phenolic Acids and Oxidative Stress Markers after Consumption of Lonicera caerulea L. Fruit

Abstract: This study investigated the effect of one-week consumption of 165 g/day fresh blue honeysuckle berries (208 mg/day anthocyanins) in 10 healthy volunteers. At the end of intervention, levels of benzoic (median 1782 vs 4156), protocatechuic (709 vs 2417), vanillic (2779 vs 4753), 3-hydroxycinnamic (143 vs 351), p-coumaric (182 vs 271), isoferulic (805 vs 1570), ferulic (1086 vs 2395), and hippuric (194833 vs 398711 μg/mg creatinine) acids by LC/MS were significantly increased in the urine. Clinical chemistry saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…20,21 It has also been suggested that majority of the hippuric acid seen in urine is due to synthesis from quinic acid present in antioxidant rich fruits. 20,21 It has also been suggested that majority of the hippuric acid seen in urine is due to synthesis from quinic acid present in antioxidant rich fruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 It has also been suggested that majority of the hippuric acid seen in urine is due to synthesis from quinic acid present in antioxidant rich fruits. 20,21 It has also been suggested that majority of the hippuric acid seen in urine is due to synthesis from quinic acid present in antioxidant rich fruits.…”
Section: Discussionmentioning
confidence: 99%
“…14 However hippuric acid is a major metabolite post polyphenol consumption that is excreted in urine in up to millimolar concentrations in vivo. [20][21][22] In spite of hippuric acid being a consistent biomarker/metabolite that can be excreted via the urine in grams per day, there are no well-documented cardiovascular benefits associated with it. According to a dietary intervention study by Toromanovic and colleagues, 16 urinary excretion of hippuric acid reached levels of up to 11 mM per 24 hours after consumption of 300 g of edible fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanidins are metabolized to phenylacetic acid (53), mono‐ and dihydroxyphenylacetic acids, mono‐ and 3,4‐dihydroxyphenylpropionic acids (54), or 4‐hydroxybenzoic acid (55). Anthocyanins are converted mainly into protocatechuic acid (56), gallic acid (57), syringic acid (58), vanillic acid (59), and phloroglucinol (60) (Crozier and others ; De Pascual‐Teresa and others ; Heinrich and others ). The similar metabolites were described also for simple organic acid (like chlorogenic acid derivatives) (Yang and others ; Breynaert and others ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Antioxidative effect of flavonoid metabolites was observed also on rat hepatocytes (Miyake and others ; Minato and Miyake ). The well‐organized study tested antioxidative effect of administration of anthocyanin‐rich rich Lonicera caerulea fruits in healthy human volunteers, and from the metabolic profiling it could be concluded that the activity is connected with the simple aromatic acids shown as metabolites (Heinrich and others ). Similar conclusions can be deduced also from study carried on human volunteers consuming chocolate which is rich in phenolic substances (Rios and others ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Blue honeysuckle berry extract has various bioactivities, including antioxidation antibacterial, anti‐inflammatory, antiproliferative, and lowering cholesterol properties (Caprioli et al, ; Celli, Ghanem, & Brooks, ; Jin et al, ; Jurikova et al, ; Liu, Wu, Guo, Meng, & Chang, ; Raudseppab et al, ; Rupasinghe, Yu, Bhullar, & BorsBob, ; Wang et al, ; Wu et al, ). These biological activities may be due to their high levels of vitamin C and polyphonic compounds, particularly anthocyanins (cyanidin‐3‐glucoside as standard; Chaovanalikit, Thompson, & Wrolstad, ; Heinrich et al, ; Wojdyło, Jáuregui, CarbonellBarrachina, Oszmiański, & Golis, ). The extraction technology of anthocyanins in blue honeysuckle berries has been investigated.…”
Section: Introductionmentioning
confidence: 99%